The effects of Gastrodia elata on anxiety-like behavior in mice - Lan-Qiao He; Jia-Yu Lin; Ming-Zhi Yu; Peng-Yu Fan; Cen-Jie He; Ting-Ting Zhao (All Life)
The present study investigated the effect of Gastrodia elata extracts (GE) on chronic electric foot-shock stress (cEFS)-induce anxiety-like behaviors in male C57BL/6 mice. Mice were administered GE (200 or 400 mg/kg/day, oral), and then exposed to cEFS (0.6 mA intensity, 1 s every 5 s interval, 3 min duration) for seven days. GE treatment ameliorates the anxiety-like behavior induced by cEFS, which were determined with elevated plus maze test and open field test. cEFS decreased the dopamine and serotonin levels in brain and both were reversed by GE treatment. cEFS increased corticosterone levels in serum and number of c-fos positive cells in brain, which were downregulated by GE treatment. These results suggested that GE ameliorates the anxiety-like behavior by regulating the levels of dopamine and serotonin, the number of c-fos positive cells in the brain, and corticosterone levels in the serum.